Complications of Recurrent Corticosteroid Use in Patients with Erythema Nodosum Leprosum : A Case Report - Muhammad Alkadri Anugrah; Eka Komarasari; Prima Kartika Esti (International Medical Journal Corp. Ltd, 2025)
The use of corticosteroids is the standard therapy for managing leprosy reactions. However, long-term corticosteroid use can cause various complications. This case report discusses the potential complications of long-term corticosteroid use in a patient with Hansen's disease (MH) and erythema nodosum leprosum (ENL) reactions. This case report emphasizes the importance of routine monitoring in patients receiving corticosteroids to detect and manage potential complications.